Analisis Strategi Kepemimpinan Dalam Perencanaan dan Penyerapan Anggaran (Studi Kasus Pada Dinas X Tahun 2018) - Nur Ratri Purnomo Wulan; Bambang Moertono S (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2019)
Absorption of the budget that is not in accordance with the targets specified in the planning may be influenced by the leadership in making budget planning, then the purpose of this study is to analyze the leadership strategy in planning and absorption of the budget. This type of research is qualitative descriptive with SWOT analysis method, by conducting interviews with echelon 4 (four) and 3 (three) officials at Dinas x with respondents as many as 15 (fifteen) people.The results of the study show that it is necessary for leaders who have competencies according to position, leadership, training in budget planning and related party coordination, monitoring evaluation of absorption, making Budget Implementation Documents as guidelines supported by financial management capabilities and additional human resources which play a role in planning and absorption of budgets.Some suggestions that can be applied at Dinas X are to improve leadership, optimal quality of planning and absorption to achieve the organization's vision, namely the realization of Sleman people who are more prosperous, independent, cultured and integrated e-Government system towards Smart Regency in 2021